Analysis of Sustainable Development of Energy Sector in Tanzania - NYAKUNGA YUSTIN MANYUSI (Graduate School of International Studies Ajou University, 2022)
Tanzania has been depending on Hydropower for past 60 years of independence however, climate change as an outcome of desertification has led to shortage of water and hence insufficient electricity generation. Due to these reasons government has been endeavoring to increase energy mix in national grid to ensure constant supply of electricity. Energy sources like natural gas, coal, geothermal, solar, wind and nuclear power are appropriate choice because of their availability within the country. With reference to Power master plan of 2032, Tanzania is looking forward to developing a number of Natural Gas, Coal, Solar and Geothermal power plants. All these projects will generate electricity with capacity equal to 10,050 MW, according to Ministry of Energy. This amount of power will significantly reduce the high dependence of traditional biomass and relatively decrease the climate change threats. The results show small quantity of carbon dioxide will be released from Natural gas and Coal power plants but this will not surpass the high ambition target of the government generally, the level of emissions will be low compared to emission reduction plan set in NDC by 2032 and the ratio of renewable and non-renewable energy sources will hit 55% and 45% respectively. The quantity of energy mix by 2032 is projected to be as follows: hydropower 49%, followed by Natural gas 29%, Coal 16% while wind, Biomass, solar and Geothermal will contribute 2 % each in contrast to current situation which only four sources of energy are installed.
학위논문(석사)--Graduate School of International Studies Ajou University :융합에너지학과,2022. 2
Keywords: Energy Sector in Tanzania